Analisis Pengendalian Kualitas Produk Dominan Produksi Printing Menggunakan Metode Control Chart Di PT. Sari Warna Asli Unit 1 Karanganyar - Kumaratih Kumaratungga Dewi; Febrina Agusti; Brillian Nur Diansari (Politeknik Kampar, 2023)
Quality control is very necessary so that the goals, plans and policies of a company in producing products are achieved. This study aims to analyze the dominant product quality control in printing production (kain sarung with construction (TR30/TR30 84 55 52)) using the control chart method at PT. Sari Warna Asli Unit 1, Karanganyar. Data collection through interviews and data processing of inspection reports. The results of data analysis obtained UCL values ??of 753, CL of 675, and LCL of 597. Gagal wanra is a defect with the highest number and is outside the control limits. The causes of these defects come from environmental factors, methods, machines, humans, and raw materials.